Conveniencia de implementar el sistema de jurados en el Ecuador - Acaro Yaguache, Carlos Julio (2012)
This research concerns one of the most serious problems in administering criminal justice in Ecuador, such as the inability to guarantee the substantive principles of independence and impartiality of judges, an issue which as we know, has not been crystallize in our country, given the tendency of political power to pollute the courts for use as a tool of domination and persecution of those who disagree with those who hold power or with the heads of the powers-that for many years have prevailed in the national territory. That is why we have emerged concern to develop a detailed study about the possibility of establishing a jury system in Ecuador as a means of promoting greater independence and impartiality in the organs of criminal, thus materializing the guarantee of due process established in Article 76, paragraph 7, letter k) of the Constitution of the Republic, to this end has developed a broad theoretical base related to the right to due process and legal certainty as premises of the constitutional state and also in the jury system, its historical origins, its evolution, its compatibility with the oral adversarial criminal process, and finally its convenience of application in the national average, according to the characteristics and needs of the administration of justice criminal, concluding that it is essential the application of the jury system as an ideal tool to strengthen participatory democracy, to engage in tasks people interact with the Judiciary, to retrieve the index of trust and credibility of the community in judges, and above all to make possible the solidification of the principles of independence and impartiality of the designated function, as a way essential to a full realization of the right to legal certainty and due process.